HARAPAN VS KENYATAAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PEMALSUAN SURAT - Rian Van Frits Kapitan; Tontji Cristian Rafael (IBLAM Law Review, 2023)
National Police Chief Regulation Number. 8 of 2021 concerning Handling of Crimes based on Restorative Justice as if or implicitly can be applied in the process of investigating and investigating criminal acts of forgery of documents in Article 263 of the Criminal Code and Article 266 of the Criminal Code. Therefore, the issue analyzed in this paper is whether the National Police Chief's Regulation on Restorative Justice can be applied to terminate investigations and investigations into criminal acts of document forgery in Article 263 of the Criminal Code and Article 266 of the Criminal Code? The purpose of this article is to find out whether or not the National Police Chief's Regulation on Restorative Justice can be applied to stop investigations and inquiries into criminal acts of document forgery in Article 263 of the Criminal Code and Article 266 of the Criminal Code. The method used in this research is a normative juridical research method with several approach methods, namely the conceptual approach method and the statutory approach method. The conclusion obtained is that the criminal act of forgery of documents in 263 of the Criminal Code and Article 266 of the Criminal Code cannot be stopped and the investigation process uses the National Police Chief's Regulations on Restorative Justice based on several reasons. First, basically the criminal act of falsifying documents is a shame in se. Second, the serious threat of imprisonment for perpetrators of the crime of document forgery. Third, stopping the investigation is in direct conflict with Article 108 paragraph (2) of the Criminal Procedure Code. Fourth, the termination of investigations and investigations is contrary to the principle of dominis litiis. Fifth, the termination of investigations and inquiries cannot be carried out because the loss paradigm in the National Police Chief's Regulations is purely material loss. Sixth, the termination of investigations and investigations is very contrary to the principle of litis finiri opportet. Seventh, the termination of investigations and inquiries does not fulfill the material requirements of restorative justice in the National Police Chief Regulations.